Don Pepe "El retrato" - Guzmán, Luis A.; Sáenz, Carlos ([San José, Costa Rica] : Centro Costarricense de Producción Cinematográfica, 1988)
Don Pepe su vida y la participación en la política nacional.
Keywords: FIGUERES FERRER, JOSÉ -- 1906-1990; VIDA POLITICA